Selinunt, Italien. Die Arbeiten des Jahres 2016 - Adorno, Linda; Albers, Jon; Bentz, Martin; Benz, Annkatrin; Dally, Ortwin; Franceschini, Mariachiara; Helfert, Markus; Miß, Axel; Müller, Jan Marius (e-Forschungsberichte des DAI, 2017)
The report includes the description of pottery from Selinunt and Megara Hyblaea, analysis using portable energy-dispersive X-ray fluorescence analysis, a final report of the excavations undertaken by the University of Bonn in the Kerameikos of Selinunt and an inventory and first analysis of materials taken from trench A, in the north-eastern part of the Agora of Selinunt.